ChemInform Abstract: Characterization Methods for Starch‐Based Materials: State of the Art and Perspectives. Issue 7 (18th February 2014) - Wu, Alex C.; Witt, Torsten; Gilbert, Robert G.
Abstract Review: 135 refs.